Gospodarka narodowa Polski. Próba oceny i warunki postępu - Wilczyński, Wacław (Wydział Prawa i Administracji UAM, 1981)
An attempt has been undertaken to view the present state of Poland's economy in a retrospective of the latest decade 1970 - 1980. The diagnosis embraces so registration of symptoms of a crisis, as causal analysis of situation worsening. In the second part of the article main conditions and ways of crisis' overcoming have been shown. There are following basic theses of the elaboration: a) the high dynamics of development in the years 1971 - 1975 was an apparent dynamics. It was not the effects dynamics but dynamics of expenditures, which did not produce expected effects; b) economic policy in the years 1976 - 1980 was full inconsistency towards still more visible symptoms of crisis accretion. It caused still deeper disproportions and the continuation of growth of the country's indebtedness; c) a main reason of discrepancies between the program and its realization was an unproper way of economy's management, causing imbalance and uneffectiveness. Such a system caused bad economy of enterprises and it weakend centrali planning. It led to the loss of state's sovereignaty over economy; d) a basic condition of extrication from the crisis is a change in the national economy functioning system, consisting in the state's withdrawal from performing „manager's" functions in favor of „regulating" functions and in introduction of a broad economic autonomy of enterpises; e) there are following premisses of the reform success: abolishment of the hither-to existing economy's institutional structure, creation of a climate promoting rational economic choice, decrease in production costa and innovation and reproduction processes in enterprises, proceeding from the ranks of the workers. The author represents then a view, that the introduction of the economic reform cannot be postponed until the moment of balance attainment, because the present system is incapable of this.
National Economy of Poland. An Attempt of Appraisal and Conditions of Progress